Influence of storage temperature and packaging materials on post-harvest quality and shelf life of moringa (Moringa oleifera) pods (Journal of the Bangladesh Agricultural University, 2020)
Moringa is one of the world’s most nutritious food and its pod remain available for the short period. Therefore, this study was undertaken to observe the performance of packaging materials and temperature on post harvest quality and shelf life of moringa pod. The two factor experiment comprised five types of postharvest packaging materials viz. P0: control, P1: perforated low density polyethylene (LDPE) bag, P2: non-perforated LDPE bag, P3: High density polyethylene (HDPE) bag and P4: brown paper and two levels of storage temperature viz. T1: ambient room  emperature (25- 280C) and T2: refrigerator condition (10-120C). The experiment was laid out in completely randomized design with three replications. The effect of packaging materials and temperature as well as their combined effects were found significant in all parameters. Results showed that the minimum weight loss, decay loss, maximum marketability and shelf life were observed in moringa stored at refrigerator condition. On the other hand, maximum weight loss, decay loss, minimum marketability and shelf life were recorded in moringa stored in ambient room temperature condition. Shelf life of pods were found 6 and 16.8 days at room and refrigerator temperature condition, respectively. In case of packaging materials, minimum weight loss, decay loss, maximum marketability and shelf life were observed in moringa pods packaging with HDPE bag; and maximum weight loss, decay loss, marketability acceptance and shelf life were recorded in moringa stored without packaging materials. Maximum shelf life (16 days) was recorded from P3 (HDPE bag) and subsequently 13 and 12 days from P2 (non-perforated LDPE bag) and P1 (perforated LDPE bag) and the minimum shelf life was 8 days from both P0 (control) and P4 (brown paper) packaging materials. Although, the acceptance of marketability is the major concern. Acceptance of marketability was more than 80% when pods were stored at refrigerated condition whereas stored at ambient condition was poor at 8 days (less than 40%). It is better to store the moringa pods at refrigerator condition with HDPE bag to consume it for long time and ensure the nutritional security.J Bangladesh Agril Univ 18(2): 316–322, 2020https://doi.org/10.5455/JBAU.80657